Increased Plasma Availability of L-arginine in the Postprandial Period Decreases the Postprandial Lipemia in Older Adults - Puga, Guilherme M. (2012)
OBJECTIVE: Older adults have exaggerated postprandial lipemia (PPL), which increases their risk for cardiovascular disease. We sought to determine the effects of increased plasma L-arginine availability on the oxidation of ingested fat (enriched with [1,1,1-(13)C]-triolein) and plasma triglyceride (TG) concentrations during the postprandial period in older subjects. METHODS: On one day, eight healthy subjects (67.8 ± 1.3 years old) received an intravenous infusion of L-arginine during the first hour of the postprandial period (L-ARG), while on a separate day they received saline (control trial; CON). RESULTS: The 8-h area under the curve (AUC(0–8h)) describing the postprandial plasma TG concentrations was considerably lower in the L-ARG trial than the CON trial (−4 ± 21 vs 104 ± 21 mg·dL(−1)·h; P < 0.01). The rate of the postprandial oxidation of the ingested lipid was not different between the trials, but the average contribution of ingested-oleate to the oleate of TG of the plasma small TG-rich lipoproteins (TRL; S(f) = 20–400) was lower in the L-ARG trial (11 ± 1 vs 18 ± 2%; P < 0.01). L-arginine infusion decreased also the AUC(0–8h) of the plasma free fatty acid concentrations derived from the ingested fat when compared to the saline infusion (0.77±0.09 vs 1.11 ± 0.08; mmol·L(−1)·h; P < 0.01). CONCLUSION: Increasing the plasma L-arginine availability during the postprandial period decreases the PPL in older adults, in association with a decrease in the postprandial contribution of ingested lipid into TG of the plasma small TRL.